Perancangan Bilah Tipe Taper pada Turbin Angin A-Wing Sumbu Horizontal - Amelia Putri Isnaeni; Ananda Kuswibawa Pratama; Aprilia Anre Ongan; Dwiki Armansyah; Muhammad Fatkhul Arifansyah; Nadiyah Damayanti; Naisya Cikal Putri Syabilah; Roikhatal Jannah; Rudi Setiawan; Sefia Rachmasari; Sofi Dwi Pratiwi; Tito Rizky Herdianto; Achmad Jauhari Widodo (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Wind Turbine Blades are one of the renewable energy sources that are the main solution to reduce excessive use of conventional fuels. Wind Turbine Blades absorb kinetic energy into mechanical energy which is then converted into electrical energy by the generator. This study uses the National Advisory Committee for Aeronautics (NACA) 1.2 horizontal axis wind turbine blade design with a taper type (having a wide base and a small tip). The initial wind turbine blade data was obtained rotating at a wind speed of 3.5 m/s with a voltage of 5.1 Volts. This blade design was carried out using maximum wind speed data of 9.5 m/s and minimum wind speed data of 3.6 m/s, then current and voltage data were obtained. The results of this study confirm that the design of this wind turbine blade affects the efficiency of converting wind energy into electricity. This taper type wind turbine blade is designed to produce optimal performance in a certain wind speed range.